Kajian Terhadap Ekspor Non Migas Paska Resesi Tahun 1998 dan Model Makro Ekspor Indonesia - -, supriyono (Universitas Sebelas Maret, 2006)
The research was aimed to discover the product of non oil export in Indonesia which have gave contribution to the value of non oil export. The value of non oil export has depent on exchange rate, foreign investment, inflation, goverment debt, and Gross Domestic Product (GDP). The research has used descriptive analysis with time series data 1999-2004. On the other side, simultaneous regression has used time series data 1970-2004.??????????? The result shows that the value of non oil export in Indonesia has depent on Gross Domestic Product (GDP) and government debt by indirect mechanism. In direct mechanism, non oil export in Indonesia has depent on exchange rate. Meanwhile, foreign investment and inflation has not significant to increase the value of non oil ekspor.?Keywords: non oil export, descriptive analysis, simultaneous regression